Dampak Transformasi Era Digital Terhadap Manajemen Sumber Daya Manusia Dalam Meningkatkan Kinerja Personel TNI-AD di Lingkungan Koramil Rungkut Surabaya - Muncahyo, Wawan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of this study is to explore the impact of digital transformation on human resource management in improving the performance of TNI-AD personnel in the Koramil Rungkut Surabaya environment. A qualitative phenomenological approach to understand the impact of digital transformation on human resource management (HR) and the performance of TNI-AD personnel at Koramil Rungkut Surabaya. The research subjects were selected through purposive sampling, involving 10 to 15 personnel with different experiences in implementing digital technology. Data were collected through in-depth interviews, participant observation, and document analysis, followed by an analysis process that included data reduction, theme grouping, and interpreting experiences. To ensure the validity of the data, the researcher applied triangulation of sources and methods and member checking with key informants. Digital transformation at Koramil Rungkut Surabaya has significantly influenced human resource management (HR) through increased operational efficiency and development of personnel capabilities. Digitalization in reporting and task management accelerates administrative processes, while technology-based training provides flexibility in competency development. In addition, digital technology encourages decentralization of organizational structures, accelerates communication, and increases individual autonomy in decision making. In the future, the role of digital technology will be increasingly important in helping the Indonesian Army face dynamic and complex modern challenges.